The Relationship Between Use of the Transmedic Application with Efficiency of Patient Registration - Dwi Handayani; Surya Darma; Melissa; Irmayani Irmayani; Rosita Ginting (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2025)
The transmedic application is a hospital management information system designed to manage patient data and support operational activities at Grandmed Hospital Lubuk Pakam. Its utilization is expected to improve the efficiency of patient registration services. This study aims to analyze the relationship between the use of the Transmedic application and the efficiency of patient registration at Grandmed Hospital Lubuk Pakam in 2025. The research employed a quantitative method with a cross-sectional design. All 33 registration officers were included as the sample using a total sampling technique. Data were collected through questionnaires and analyzed using the chi-square test with a significance level of 0.05. The results indicated that the majority of respondents (54.5%) used the Transmedic application optimally, with the same percentage reporting high efficiency in patient registration. Statistical testing revealed a significant relationship between the use of the Transmedic application and the efficiency of patient registration services (p = 0.001 < 0.05). It is recommended that hospital management optimize the use of the Transmedic application by improving infrastructure, ensuring the availability of adequate devices, stable internet connections, and regular system maintenance to prevent technical obstacles.